A pyridoindole antioxidant SMe1EC2 regulates contractility, relaxation ability, cation channel activity, and protein-carbonyl modifications in the aorta of young and old rats with or without diabetes mellitus - Sayın Şakul, Arzu; Arı, Nuray; Sotnikova, Ruzenna; Ozansoy, Gülgün; Karasu, Çimen (Springer, 2018)
We studied the effects of treatment with SMe1EC, a hexahydropyridoindole antioxidant, on vascular reactivity, endothelial function, and oxidonitrosative stress level of thoracic aorta in young and old rats with or without diabetes mellitus. The rats were grouped as young control (YC 3 months old), old control (OC 15 months old), young diabetic (YD), old diabetic (OD), young control treated (YCT), old control treated (OCT), young diabetic treated (YDT), and old diabetic treated (ODT). Diabetes was induced by streptozotocin injection and subsequently SMe1EC2 (10 mg/kg/day, p.o.) was administered to YCT, OCT, YDT, and ODT rats for 5 months. In young and old rats, diabetes resulted in hypertension, weight loss, hyperglycemia, and hypertriglyceridemia, which were partially prevented by SMe1EC2. SMe1EC2 also inhibited the diabetes-induced increase in aorta levels of AGEs (advanced glycosylation end-protein adducts), 4-HNE (4-hydroxy-nonenal-histidine), 3-NT (3-nitrotyrosine), and RAGEs (receptors for AGEs). The contractions of the aorta rings to phenylephrine (Phe) and KCL did not significantly change, but acetylcholine (ACh) and salbutamol relaxations were reduced in OC compared to YC rats. Diabetes induction increased Phe contractions in YC and OC rats, KCL contractions in YC rats, and did not cause further inhibition in already inhibited ACh and salbutamol relaxations in OC rats. We have achieved the lowest levels of ACh relaxation in YD rats compared to other groups. SMe1EC2 did not change the response of aorta to ACh, salbutamol and Phe in YC rats, and ameliorated ACh relaxations in OC and YD but not in OD rats. In YDT and ODT rats, increased Phe and KCL contractions, high blood pressure, and impaired salbutamol relaxations were amended by SMe1EC2. Phe contractions observed in YD and OD rats as well as KCl contractions observed in OC rats were the lowest levels when the rats were treated with SMe1EC2. When the bath solution was shifted to cyclopiazonic acid (CYP) or CYP plus Ca2+-free medium, the contraction induced by a single dose of Phe (3 x 10(-6) M) was more inhibited in YD and OD than in YC but not in OC rats. In SMe1EC2-treated rats, neither the presence of CFM nor CFM plus CYP exhibited a significant change in response of aorta to a single dose of Phe. These findings suggest that alpha 1-adrenergic receptor signaling is activated in both age groups of diabetic rats, diabetes activates K+-depolarization and calcium mobilization via Ca-V especially in the aorta of young rats, and sensitizes the aorta of old rats to the regulating effect of SMe1EC2. ACh relaxations were inhibited in YC rats, increased in OC rats and unchanged in YD and OD rats when aortic rings pretreated with TEA, an inhibitor of calcium-activated K+ channels (K-Ca), or 4-aminopyridine (4-AP), an inhibitor of voltage-sensitive K+ channels (K-V). ACh relaxations were inhibited in YCT, OCT, and YDT rats in the presence of 4-AP or TEA. In ODT rats, 4-AP did not change ACh relaxation but TEA inhibited. These findings suggest that the contribution of K-v and K-Ca to ACh relaxation is likely upregulated by SMe1EC2 when the relaxations were inhibited by aging or diabetes. We conclude that SMe1EC2 might be a promising agent for aging and diabetes related vascular disorders.
WOS: 000444557200004
PubMed ID: 30054861
Keywords: Aging; Diabetes; Antioxidant; Aorta; Pyridoindole; Rat; Protein Carbonylation; Oxidonitrosative Stress; Contractility; Endothelium